Effect of the support properties in dehydrogenation of biphenyl-based eutectic mixture as liquid organic hydrogen carrier (LOHC) over Pt/Al2O3 catalysts. (15th January 2021) - Kwak, Yeonsu; Moon, Seongeun; Ahn, Chang-il; Kim, Ah-Reum; Park, Yongha; Kim, Yongmin; Sohn, Hyuntae; Jeong, Hyangsoo; Nam, Suk Woo; Yoon, Chang Won; Jo, Young Suk
Graphical abstract: Highlights: A biphenyl-based eutectic mixture (H12-BPDM, 6.9 wt% of H2 ) is utilized as a LOHC. 0.5 wt% Pt/Al2 O3 catalysts were fabricated with 6 commercial Al2 O3 pellets. Dehydrogenation performances were evaluated at various operating conditions. Catalysts characterizations over the effect of Al2 O3 supports were investigated. Abstract: Biphenyl-based eutectic mixture (BPDM, 35 wt% Biphenyl, and 65 wt% Diphenylmethane) has gained attraction as a strong candidate for liquid organic hydrogen carriers (LOHC) particularly due to the high hydrogen capacity (6.9 wt%). To take full advantage of its capacity, facile and high-extent dehydrogenation with reversibility is the key, where the appropriate selection of supports in heterogeneous catalysts plays a crucial role. Herein, the effect of the properties of commercial Al2 O3 pellets in the dehydrogenation reaction of a hydrogenated biphenyl-based mixture (H12-BPDM) over Pt/Al2 O3 catalysts is investigated. H2 production rate, 10 h performance tests, and product composition from the dehydrogenation of H12-BPDM are evaluated with the in-house catalytic screening tests using continuous fixed-bed reactors. Catalyst characterization and product analysis suggest that pore size distributions and corresponding surface properties of Al2 O3 supports can lead to different dehydrogenation reaction characteristics of H12-BPDM. This study provides a rationale for the proper support selection for efficient utilization of BPDM as a LOHC.